OFR-1-82 Environmental Test Criteria For The Acceptability Of Mine Instrumentation - Kenneth Trelewicz (The National Institute for Occupational Safety and Health (NIOSH), 1981)
This report describes the total effort that went into developing environmental test criteria for general mine instrumentation. The project was a two-phase effort. Phase I consisted of research and mine visits to develop an environmental profile for mine instrumentation. The profile was translated into general requirements and then into test requirements. A review of existing government and commercial specifications was performed to determine if they matched mine instrumentation test requirements. Finally, a set of environmental test procedures was developed for the testing of mine instrumentation. Phase II consisted of selecting and purchasing sample mine instrumentation and subjecting them to the previously developed tests. The purpose was twofold: (1) to evaluate the criteria developed for use as an instrumentation test document and (2) to determine the effects of the various criteria on a representative sample of both proven and newly developed instrumentation. The test criteria were then modified, based on the results of the testing, and are listed therein.